ANALYSIS OF AMINE HARDENERS FOR ADHESIVE USING pH-METRIC TITRATION IN MICELLAR MEDIA OF SODIUM DODECYLSULFATE: DOI: https://doi.org/10.17721/1728-2209.2020.1(57).7 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
One of the primary tasks in the development of amine hardeners for adhesive and epoxy resins is the control of amino group quantities in their composition. The main parameter that indicates the rate of the polymerization reaction and characterizes the quality of the hardener is the amine number. It is determined by the number of primary and secondary amino groups contained in the hardener molecule, because these functional groups are involved in reactions with epoxy resins. The most common methods of analysis of amine hardeners are mainly based on titration in organic solvents and require a procedure of derivatization of primary and secondary amino groups using formaldehyde and acetic anhydride. The search for a simple, cheap and environmentally friendly alternative to such titrimetric methods is still ongoing.In this paper on the example of industrial samples of polyamide PO-300, polyethylene polyamine (PEPA) and diethylenetriamine (DETA) shows the prospects of using the method of pH-metric titration in water-micellar medium of sodium dodecylsulfate (SDS) to determine the content of primary and secondary amino groups in the adhesive hardeners. According to the developed techniques, working solutions of PO-300, PEPA and DETA were prepared by dissolving their exact mass in 20 ml of 2.0 M SDS solution. The values of PO-300, PEPA and DETA samples were 0.1040 g, 0.0225 g and 0,0200 g, respectively. Titration of the obtained solutions was performed with 0.05 M HCl solution. The percentage of primary amino groups, calculated on the basis of the obtained differential titration curves, is equal to 5,56% for PO-300, 23,6% for PEPA and 31,6% for DETA. The content of secondary amino groups in PO-300, PEPA and DETA samples is 3,03%, 15,0% and 19,6%. Founded amine number for PO-300, PEPA and DETA is well correlated with data declared by the manufacturer and equals to 302, 1381 and 1890, respectively. Unfortunately, it was not possible to establish the presence and quantity of tertiary amino groups in the samples of adhesive hardeners by this technique.The effect of cationic surfactant cetylpyridinium chloride, nonionic Triton X-100 and anionic surfactant SDS on the value of the pH jump of diethylenetriamine (DETA) was also studied. It was found that anionic SDS has the greatest differentiating effect on the acid-base properties of amino groups DETA in comparison with other studied surfactants. At that, the primary amino groups are titrated in the first place.
Keywords: amino group quantities, amine hardeners, titration, aqueous micellar media.